1998
DOI: 10.1007/bf01452257
|View full text |Cite
|
Sign up to set email alerts
|

HLA B27: A prognostic factor in juvenile chronic arthritis

Abstract: This study was performed to assess the frequency of HLA B27 in patients with juvenile chronic arthritis (JCA) of varying severity and outcome by studying three patient categories: those in whom cytostatic treatment with azathioprine had been started, those with secondary amyloidosis, and those with arthroplasty of the knee or hip joints. In the first category the frequency of the HLA B27 allele was compared between those who had attained remission and those who had not. In the second and third categories the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…This finding is in agreement with Berntson et al . Other studies have also shown HLA‐B27 to be associated with a more destructive disease and difficulty in achieving remission when compared with other categories . However, to the best of our knowledge, no study has reported HLA‐B27 as a predictor for biologic treatment in ERA patients.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in agreement with Berntson et al . Other studies have also shown HLA‐B27 to be associated with a more destructive disease and difficulty in achieving remission when compared with other categories . However, to the best of our knowledge, no study has reported HLA‐B27 as a predictor for biologic treatment in ERA patients.…”
Section: Discussionsupporting
confidence: 91%
“…IgM‐RF–positive patients with JIA are known to have a disease course similar to that of adult RA, and HLA–B27–positive patients (boys with disease onset beyond 8 years of age and with enthesitis and arthritis) are thought to have a disease course similar to that in adults with ankylosing spondylitis. One other study has also indicated that HLA–B27 positivity in JIA patients relates to a more severe course of JIA (39).…”
Section: Discussionmentioning
confidence: 96%
“…4 The overall frequency of HLA B27 in the Finnish population is as high as 14.5% and among JIA patients it is about 30%. 5 Among patients with asymptomatic uveitis, arthritis began earlier and ANA positivity was more common than among those without uveitis. Also, positive HLA B27 was found more often in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of JIA has interested many researchers during the past three decades. [5][6][7][8][9] However, only limited information is available on the prognosis of uveitis in JIA patients reaching adulthood. In a recent Danish 25 year retrospective study, uveitis had occurred in 10 of 65 adult patients with juvenile arthritis; the eye inflammation was persistent or chronic in three of these.…”
mentioning
confidence: 99%